Proverbs 31 in dialogue with Acts 9:36–43: An Afro-feminisation of Mother Earth for equity - Juma, Dorcas C. (HTS teologiese studies, 2023)
A close relationship between masculinity, alcoholism, widowhood and gendered poverty is evident in contemporary African society. Alcohol consumption among young men begins at an increasingly early age due to availability of low-priced alcohol presented in different varieties. Young, beautiful and sexy girls are used to advertise alcohol. Many young men are addicted to alcohol and totally unable to be free from alcohol addiction. This sad state coupled with the impact of globalisation on the economies of many African countries has left many men jobless. Consequently, many households are headed by women in a patriarchal context where men are supposed to be the heads of the family. Through an Afro-feminisation of Mother Earth lens, this article re-read Proverbs 31 in dialogue with Acts 9:36–43, to show the role of women in the socio-economic sustainability of the family, society and in enhancing gender equity.Contribution: This article re-read Proverbs 31 in dialogue with Acts 9:36–41 as resources for enhancing gender equity. An Afro-feminisation of Mother Earth for sustainable development was presented in ways that open up possibilities for the life of the Garden of Eden in Genesis 1:28 to flourish.